L'albero della vita Feste religiose e ritualità profane nel mondo globalizzato - Scotti, Simona; Lucà Trombetta, Pino (Atti, 2007)
The feast represents the quintessence of time, distinguished from time in general by a potent intensity. The dynamics of secularisation have attenuated and blurred the boundaries between sacred and profane, to the point that we ask ourselves if it is still legitimate to distinguish between a religious and a profane feast, or whether it is not more proficuous to seek within the feast the sacred dimension of time. Modernity does not lead to the eclipse of the sacred, but rather to its transformation. This book addresses such issues, putting itself forward as a working tool for further study.